Phytochemistry of Aloe vera: A Catalyst for Environment-Friendly Diverse Nanoparticles with Sustained Biomedical Benefits - Yadav, S.; Khan, A.; Sharma, J. G. (Nature environment and pollution technology, 2025)
Nanotechnology has become one of the most active fields in the research area and is getting more attention toward nanoparticle synthesis. Green synthesis methods using various plants, fungi, bacteria, and algae were used to synthesize nanoparticles with proper requirements and maintain sterile conditions to get the desired products. Aloe vera, a bio-medicinal plant, contains a wide range of phytochemicals such as phenolic, hydroxyl groups, alkaloids, polyols, polysaccharides, etc, which act as reducing and capping agents with high efficiency. This review revealed that aloe vera-derived nanoparticles are safe, stable, cost-effective, and eco-friendly, and they also possess significant applications for drug targeting, disease resistance, tissue engineering, wound healing, anticancer, antibacterial, and cosmetic industries. Synthesized metal nanoparticles are characterized through UV-visible spectroscopy, X-ray diffraction, scanning electron and transmission electron microscopy, photoluminescence, and the Well-diffusion method. It is highly interesting to note that aloe vera-mediated silver and zinc nanoparticles possess high potency against multi-drug resistant pathogens. Here, anticancer, antioxidant, anti-inflammatory, and photocatalytic activity separately showed by aloe vera peel, gel, and leaf, along with possible challenging situations faced during plant extract-based nanoparticle synthesis, are highlighted. Additionally, the introduction of GMOs is subjected to play an important role in advancing green methods. However, more research is required to estimate the dose’s safety, degradation, and synergistic mechanism inside the human body for better use of the green method for the treatment of microbial infections.